Upaya pencegahan sindrom metabolik dan obesitas melalui perubahan pola eating habits, screen-based activities serta peningkatan aktivitas fisik pada anak dan remaja - Eka Febri Zulissetiana; Budi Santoso; Syifa Alkaf; Puji Rizki Suryani; Andra Kurnianto (Fakultas Kedokteran Universitas Sriwijaya, 2020)
Prevention of metabolic syndrome and obesity through modification of eating habits, screen based activities and physical activities in children and adolescents. Obesity in childhood and adolescence is considered as one of the serious health problems in the 21st century. Obesity is a serious concern because the prevalence is increasing every year. Providing correct understanding to the community and training for Posyandu cadres is an appropriate way to prevent an increase in new cases of obesity. This community service activity was carried out in the city of Palembang, South Sumatra. Counseling about obesity is done to 87 teenagers and 45 adults. Training and assistance on how to measure BMI are also carried out for 10 Posyandu cadres. An evaluation of the success of the activity is carried out using random questions to the participants before and after the activity. After community service activities, most Posyandu participants and cadres understand about obesity in children and adolescents and how to prevent it. From this community service, it can be concluded that counseling and training can be used to improve the knowledge and skills of the community and cadres in recognizing and preventing obesity in children and adolescents.